Block Copolymers: Laterally Ordered Sub‐10 nm Features Obtained From Directed Self‐Assembly of Si‐Containing Block Copolymer Thin Films (Small 48/2015). Issue 48 (December 2015) - Rho, Yecheol; Aissou, Karim; Mumtaz, Muhammad; Kwon, Wonsang; Pécastaings, Gilles; Mocuta, Cristian; Stanecu, Stefan; Cloutet, Eric; Brochon, Cyril; Fleury, Guillaume; Hadziioannou, Georges
Abstract : On page 6377, K. Aissou, G. Hadziioannou, and co‐workers report the directed self‐assembly of Si‐containing block copolymer thin films on laser‐inscribed azobenene‐containing layers. These are shown to be useful to produce laterally ordered sub‐10 nm features. One potential application for this processing technology is towards next‐generation lithography, for instance, highly ordered 2D arrays of out‐of‐plane cylinders with an areal density of 2.9 teradots inch −2 are demonstrated.